Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 56976 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Passifloraceae", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 56976 records from 228 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000173-150316153013904/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences